2007
DOI: 10.1111/j.1530-0277.2007.00483.x
|View full text |Cite
|
Sign up to set email alerts
|

Dose‐ and Time‐Dependent Expression of Anxiety‐Like Behavior in the Elevated Plus‐Maze During Withdrawal From Acute and Repeated Intermittent Ethanol Intoxication in Rats

Abstract: Withdrawal from a single exposure to ethanol produces transient but significant anxiety-like behavior, and repeated intermittent bouts of intoxication result in a significant extension of the duration of effect. The rapid emergence and progression of negative emotional signs of withdrawal may be a significant factor in determining susceptibility to transition from casual drinking to loss of control and escalating patterns of consumption that result in alcoholism.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
50
0
3

Year Published

2007
2007
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 60 publications
(54 citation statements)
references
References 71 publications
1
50
0
3
Order By: Relevance
“…Acute exposure to a high dose of alcohol reliably produces increases in anxiety-like behavior (Zhang et al, 2007) and a negative emotional state as measured by brain stimulation reward thresholds (Schulteis and Liu, 2006). These effects are amplified after multiple ethanol exposures (Schulteis and Liu, 2006;Zhang et al, 2007), suggesting a role for negative emotional states during early-stage alcohol use and in the subsequent transition to addiction.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Acute exposure to a high dose of alcohol reliably produces increases in anxiety-like behavior (Zhang et al, 2007) and a negative emotional state as measured by brain stimulation reward thresholds (Schulteis and Liu, 2006). These effects are amplified after multiple ethanol exposures (Schulteis and Liu, 2006;Zhang et al, 2007), suggesting a role for negative emotional states during early-stage alcohol use and in the subsequent transition to addiction.…”
Section: Discussionmentioning
confidence: 99%
“…Acute exposure to a high dose of alcohol reliably produces increases in anxiety-like behavior (Zhang et al, 2007) and a negative emotional state as measured by brain stimulation reward thresholds (Schulteis and Liu, 2006). These effects are amplified after multiple ethanol exposures (Schulteis and Liu, 2006;Zhang et al, 2007), suggesting a role for negative emotional states during early-stage alcohol use and in the subsequent transition to addiction. A similar correspondence has been observed in studies of opioid withdrawal where both rat and human studies have validated that acute withdrawal after single doses of drug mimics much of the pharmacology of acute withdrawal after chronic drugs (Stitzer et al, 1991;Schulteis et al, 2003).…”
Section: Discussionmentioning
confidence: 99%
“…The similarity in GABA A R alterations after chronic or single dose EtOH suggests that withdrawal symptoms should be detectable after single dose EtOH. Indeed, transient decreases in seizure thresholds (Goldstein, 1972;Mucha and Pinel, 1979) and heightened anxiety (Doremus et al, 2003;Zhang et al, 2007) have been documented after single-dose EtOH intoxication in rodents. Although we are unaware of published reports, it seems reasonable to suggest that transient sleep disturbances should also be detectable after a single intoxicating EtOH dose.…”
Section: Discussionmentioning
confidence: 99%
“…The elevated plus maze was utilized in the present study because it was previously shown to be a sensitive index of anxiety-like behavior accompanying antagonistprecipitated withdrawal from chronic opioids (Higgins and Sellers, 1994;Schulteis et al, 1998). In addition, this model has been shown to produce consistent anxiety-like behavioral profiles during withdrawal from both chronic and acute ethanol exposure (Baldwin et al, 1991;Doremus et al, 2003;File, 1994;Valdez et al, 2004;Zhang et al, 2007). Although the elevated plus maze is a novelty-based task that requires a between-subjects approach, a withinsubjects approach is not optimal when seeking to study the withdrawal response to a single acute opioid treatment; moreover, our previous work has shown that conditioned withdrawal responses may contribute to the magnitude of naloxone-precipitated withdrawal if animals are repeatedly tested under both acute and repeated intermittent morphine conditions (Schulteis et al, , 2005.…”
Section: Introductionmentioning
confidence: 99%
“…It is noteworthy that brain reward deficits and anxiety-like behavior during withdrawal from acute morphine closely parallel negative emotional consequences of withdrawal from acute ethanol Schulteis and Liu, 2006;Zhang et al, 2007). Throughout these studies it has been clearly demonstrated that a single exposure to morphine or alcohol is sufficient to induce a state of acute dependence as measured by negative emotional indices of withdrawal, and severity of said negative emotional withdrawal is further potentiated with several repeated intermittent daily or weekly exposure to opioids or ethanol, suggesting rapid induction and progression of neuroadaptation within brain emotional and reward circuitry.…”
mentioning
confidence: 99%